Social and Spill-Over Benefits as Motivating Factors to Investment in Formal Education in Africa: A Reflection around Ghanaian, Kenyan And Rwandan Contexts. - S.Y.Ampofo; B. Bizimana; I. Ndayambaje; V. Karongo; K. Lyn Lawrence; J. A. Orodho (University of Cape Coast, 2015)
This study examined the social and spill-over benefits as motivating factors to investment in formal education in selected countries in Africa. The paper had three objectives, namely) to profile the key statistics of formal schooling; ii) examine the formal education and iii) link national goals of education with expectations in Ghana, Kenya and Rwanda. The major contention of the paper is that investment in education is not a matter of random choice but rather an imperative led by the fact that education holds returns and externalities to the largest society. Authors reviewed theory of human capital, local and international publications on social and spill over benefits of education focusing on Ghana, Kenya and Rwanda. The analysis of government policies and other publications from these three African nations have shown that education is considered as a key sector in these developing nations. Nevertheless, the researchers found out that mostly only primary and secondary education are distinctively accorded considerable public financial resources which might be associated with the countries limited financial ability, competitive needs, national and global trends. However, the fact that Ghana, Kenya and Rwanda strive to become democratic, self-reliant and middle income nations by conquering long terms set visions in which caliber manpower, welfare, self-employment, reduced social inequalities, increase in average income, knowledge based society, ICT driven and sustainable economy are key characteristics; it is imperative to invest substantially in TVET and higher education. It is also recommended that Ghana, Kenya and Rwanda put in place strong institutions that objectively, effectively and rationally ensure the efficient use of all available resources towards maximum educational outputs (265 words).
147p,; ill
Keywords: Social Benefits; Spill-over Benefits; Private Cost; Social Cost; Private Rate of Returns; Education; Cost- Best Analysis in Education; Africa; Ghana; Kenya; Rwanda.